An overview of organ donation for support staff. Issue 7 (2nd July 2019) - Bleakley, Gregory
Abstract : The purpose of this article is to outline the importance of organ and tissue donation as a normal part of end-of-life care. Organ-donation statistics are presented, which highlight the need for more donors. Many healthcare assistants (HCAs) and registered nurses are involved in the care of dying and deceased patients. This article intends to equip the HCA with knowledge of key terms and best practice concerning the organ- and tissue-donation process. Grief response is briefly explored and the importance of collaborative working is discussed. A framework for best practice is presented to enhance the likelihood of a positive donation outcome.